The politics of identity in Indonesia: Results from political campaign advertisements - FOX, Colm A. (Institutional Knowledge at Singapore Management University, 2011)
Despite the many benefits of democracy, a number of scholars have cited the dangers of introducing democratic elections in ethnically divided states. One of the biggest fears is the politicization of identity. However, very little research has systematically studied the particular conditions that compel politicians to make identity appeals. Taking the case of an ethnically diverse new democracy, Indonesia, this paper attempts just that. To measure identity appeals it takes the novel approach of drawing on political campaign posters. Between 2009 and 2011 over 4,000 political campaign posters were gathered from legislative and executive elections across hundreds of electoral districts in Indonesia. These posters were then individually coded for identity and non-identity related symbols, messages, and appeals. This methodological approach takes the form of a natural experiment. Because elections in Indonesia use different electoral rules (PR, Semi-PR, and Plurality), it allows us to compare the kinds of appeals made under different electoral rules while holding the region constant. Findings show that identity appeals are much more common under plurality electoral rules compared to PR rules; religious appeals were most common in districts where there are two-to-three large religious groups; and nationalist appeals are least common in regions that have had historical rebellions against the state. Beyond that, this research shows how political parties, urbanization, and the sex of a candidate can influence identity appeals.